Interleukin 37 Suppresses M1 Macrophage Polarization Through Inhibition of the Notch1 and Nuclear Factor Kappa B Pathways - Zhou, Peitao; Li, Qianqin; Su, Shuwen; Dong, Wenhui; Zong, Suyu; Ma, Qiong; Yang, Xi; Zuo, Daming; Zheng, Shaoyi; Meng, Xianzhong; Xu, Dingli; Zeng, Qingchun (Frontiers in Cell and Developmental Biology, 2020)
Macrophage-orchestrated chronic inflammation plays an important role in cardiovascular disease, including accelerating the development of calcific aortic valve disease (CAVD). M1 and M2 macrophage polarization imbalances can alter intensity of inflammatory responses. Recombinant human interleukin 37 (IL-37) could be involved in regulating immune cell function to attenuate inflammation. This study aimed to identify IL-37 specifically modulates M1 polarization and investigate the underlying mechanism. Compared with normal valves, there are more M1 macrophages accumulation and less IL-37 expression in calcific aortic valves, which may indicate a negative relationship between IL-37 and M1 polarization. THP-1 cells could differentiate into resting macrophages with phorbol-12-myristate-13-acetate (PMA) and then polarize into M1 macrophages following treatment with lipopolysaccharide (LPS) and interferon gamma (IFN-γ). In vitro, recombinant human IL-37 attenuated the expression of inducible nitric oxide synthase (iNOS), CD11c, IL-6 and monocyte chemoattractant protein 1 (MCP-1) in M1 but augmented the expression of CD206 and IL-10 in M2. The suppression of M1 polarization was associated with the inhibition of the activation the nuclear factor kappa B (NF-κB) and Notch1 signaling pathways. These results demonstrated that IL-37 inhibits the macrophages polarizing into M1 type via the inhibition of the Notch1 and nuclear factor kappa B pathways. In summary, IL-37 could be a potential therapeutic candidate for progressive CAVD by modulating M1 polarization and its orchestrated inflammation.